Working time, satisfaction and work life balance: A European perspective - Stephan Humpert (SPOUDAI - Journal of Economics and Business, 2014)
This paper analyses gender-specific differences in working time mismatches by using three different measures for representing satisfaction and work life balance. Results show that, while male satisfaction with life or work is in general not affected by working for more or less hours, over-time is found to significantly lower male work life balance. Women are more sensitive to the amount of working hours as they prefer part-time employment and they are dissatisfied with changes towards working more or less hours than agreed.
Keywords: J22; I31; J16; 330; Working Hours; Gender Differences; Work Life Balance; European Social Survey